Kingdom of Lesotho Education Public Expenditure Review - World Bank (World Bank, Washington, DC, 2019)
This Public Expenditure Review (PER) is the result of a collaboration among the World Bank Group, and Lesotho’s Ministries of Education and Finance, and is designed to inform Lesotho’s effort in expanding access to quality education services, while operating in a highly fiscally constraint environment. Although education spending is one of the highest in the world as a percentage of GDP (13.5 percent of GDP) and universal access to primary education enshrined in law, poor educational outcomes persist across the country. Lesotho is also not on track to achieve the two education-related MDGs, with both primary enrollment (82 percent) and primary completion (65 percent) rates lagging far behind the goal of 100 percent by the end 2015. The report is organized as follows. The first chapter offers a detailed assessment of the overall sectoral budgeting and expenditure patterns in the education sector over a five-year period, from fiscal years (FY) 2011-12 to 2015-16, using multiple data sources. The second chapter estimates the cost of expanding secondary education to achieve the government’s goal of universal compulsory lower basic education by 2020 and makes recommendations on how to better utilize the funding for the sector taking into account the fiscal constraints at macro level.